Fostering the Love of Reading: Dynamics and Sustainability of Book Clubs in Indonesian Universities - Irfan Rifai; Anesti Budi Esmerawati; Rusiana Rusiana; Lanoke Intan Paradita; Christina Lhaksmita Anandari; Ahriyana S Pattiwael (Bina Nusantara University, 2023)
The research aimed to reveal the dynamics of the book clubs that the researchers started with and for Indonesian EFL (English as a Foreign Language) students at the university level, as well as the club's impacts on students' learning. Book clubs were essential in nurturing students' reading habits as a community. Studies found that book club activities affected one’s engagement in reading by giving readers the voice, room to participate actively, social support, and the choice to decide what they read. Indonesian university students in the EFL context faced reading engagement issues; the researchers initiated book clubs with the unified mission of growing students' love of reading and forming good reading habits. The research reported a qualitative study of a group of Indonesia Extensive Reading Association (IERA) members sharing reflections on establishing and managing book clubs or literature circles in six universities in Indonesia where the researchers taught. The data of participants' reflections were gathered and analyzed iteratively to find common themes or patterns. As a result, the research finds that the book club activities have fostered the love of reading and inferred the empowerment of collaboration, communication, creativity, and critical thinking. The research also reveals that in setting up a book club at the university level, the support of the university and the readers' community and extended networks are needed. For a book club to sustain itself, four aspects must be considered: participants' involvement, product-oriented activities, voluntarism of participants, and rewards.